Gut microbiome and metabolomics in systemic sclerosis: feature, link and mechanisms - Yao, Qicen; Tan, Wenfeng; Bai, Feihu (Frontiers in Immunology, 2024)
Systemic sclerosis (SSc) is a rare and highly heterogeneous chronic autoimmune disease characterized by multi-organ and tissue fibrosis, often accompanied by a poor prognosis and high mortality rates. The primary pathogenic mechanisms of SSc are considered to involve tissue fibrosis, autoimmune dysfunction, and microvascular abnormalities. Recent studies have shed light on the gut microbiota (GM) and metabolites in SSc patients, revealing their association with gastrointestinal symptoms and disease phenotypes. However, further elucidation is needed on the specific mechanisms underlying the interactions between GM, metabolites, and the immune system and their roles in the pathogenesis of SSc. This review outlines the characteristics of GM and metabolites in SSc patients, exploring their interrelationships and analyzing their correlations with the clinical phenotypes of SSc.The findings indicate that while the α-diversity of GM in SSc patients resembles that of healthy individuals, notable differences exist in the β-diversity and the abundance of specific bacterial genera, which are closely linked to gastrointestinal symptoms. Moreover, alterations in the levels of amino acids and lipid metabolites in SSc patients are prominently observed and significantly associated with clinical phenotypes. Furthermore, this review delves into the potential immunopathological mechanisms of GM and metabolites in SSc, emphasizing the critical role of interactions between GM, metabolites, and the immune system in comprehending the immunopathological processes of SSc. These insights may offer new scientific evidence for the development of future treatment strategies.